DAUGHTER ABUSE IN AFRICAN-AMERICAN FAMILY AS REFLECTED IN SAPPHIRE’S PUSH - PARAMITRA, PUSPA DIO (Jurnal Ilmiah Mahasiswa FIB, 2014)
Paramitra, Puspa Dio. 2014. Daughter Abuse in African-American Family asReflected in Sapphire’s Push. Study Program of English, Universitas Brawijaya.Supervisor: Sri Herminingrum; Co-Supervisor: Fariska Pujiyanti. Patriarchal system is father’s domination to control his family member. Father has to fulfill the duty because he is the family leader. However, in Push, the disorganization happens among Black people and it comes from a little scope, family. It is because the roles of family members are different. Superiority represented by father and mother, and inferiority represented by daughter. Their position makes them push the inferior by abusing their daughter.This study uses feminism approach to analyze African-American womenwho face the problem of domestic abuse in Push Novel. Patriarchal system andwoman subordination are used to analyze the data about domination by parentstoward daughter. While theory of abuse is used to analyze the kinds of abuse that happen to the main character as inferior.The result of this research reveals that there are four abuses that happen tothe main character, Claireece, i.e., as neglect, emotional abuse, physical abuse,and sexual abuse. The impact makes Claireece has problem in her life like being illiterate and pregnant. The next researcher can use psychological aspect to find the causes and impacts of Black parents who abuse their daughter therefore deeper comprehension toward African-American family can be obtained. Keywords: family, parents, daughter abuse.